The East German wage structure after transition - Robert Orlowski; Regina T. Riphahn (Center for Economic Studies and ifo Institute (CESifo), 2008)
We extend the literature on transition economies' wage structures by investigating the returns to tenure and experience. This study applies recent panel data and estimation approaches that control for hitherto neglected biases. We compare the life cycle structure in East and West German wages for fulltime employed men in the private sector. The patterns in the returns to seniority are similar for the two regional labor markets. The returns to experience lag behind in the East German labor market, even almost 20 years after unification. The results are robust when only individuals are considered who started their labor market career in the market economy and they hold across skill groups.
Keywords: J31; J24; 330; Wage structure; life cycle earnings; returns to tenure; returns to experience